A legal analysis on the water resources management in Malaysia / Nur Khalis Johar Amin, Siti Noor Mardiana Shahrom and Nurfarahin Mohd Karim - Johar Amin, Nur Khalis; Shahrom, Siti Noor Mardiana; Mohd Karim, Nurfarahin (2011)
This research is a legal analysis on water resources management in Malaysia. There are two branches of water management in Malaysia which is water resources and water supply and sewerage services management. However, this study aims to discover the problems with regards to the water resources management in Malaysia, in particular, whether numerous water-related laws and departments in Malaysia is the main problem that lead to numerous problems with regards to water resources management. In Malaysia, problems correlated with water resources management include non revenue water, uncontrolled development and fragmented powers and jurisdictions of public authorities. In order to solve all of these problems, we recommended that Malaysia should adopt the model of the Integrated Water Resources Management (IWRM) where it aims to promote coordination of the development and management of water, land and related resources in order to maximise the resultant economic value and social welfare in an equitable manner without compromising the sustainability of vital ecosystems. In United Kingdom, this model was introduced as the River Basin Management. In Selangor, there is also a single body which was established under the LUAS Enactment 1999 by the State Government of Selangor which was inspired by the River Basin Management in UK. IWRM policy is currently implemented on the river basin of Selangor. If it is successful, Lembaga Urus Air Selangor (LUAS) may be a perfect model that should be adopted by all other states in Malaysia.